REAKSI PASAR SAHAM TERHADAP PENGUMUMAN KRISIS FINANSIAL GLOBAL (Studi pada Perusahaan Pertambangan yang Masuk Dalam LQ45) - Hariyo Subekti Utomo Prasojo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study aimed to determine the market's reaction to the events of the global financial crisis on 7 September 2008. This study used two sample of its coal mining company in the period April to September 2008. From these study it can be seen if the global financial crisis responses by the market and generate significant negative abnormal returns after the event date, although from test analysis the average abnormal return before and after the global financial crisis, the average yield was not significantly different. And from test average trading volume yielded an average activity significantly different. Keywords: global financial crisis, market's reaction, abnormal return, trading volume activity.